2018
DOI: 10.1111/avsc.12354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prescribed fire and cutting as means of controlling the invasion of sub‐alpine grasslands by Echinospartum horridum

Abstract: Aims: Sub-alpine grassland ecosystems have some of the highest biodiversity in Europe and constitute high-value natural resources. These grasslands are under threat because of the abandonment of traditional agro-pastoral activities and subsequent invasion by woody species. In the Central Pyrenees (Spain) several management techniques have been used to stop expansion of the highly encroaching shrub Echinospartum horridum. However, the ways in which these techniques affect recovery of sub-alpine grasslands are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Mechanical removal is much more effective than fire because these two types of removal differently affect the seed establishment rates of E. horridum on bare soil (Nuche et al, 2018). Fire perturbation increased E. horridum seedling establishment more than clearing as also reported previously (Nuche et al, 2018).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Mechanical removal is much more effective than fire because these two types of removal differently affect the seed establishment rates of E. horridum on bare soil (Nuche et al, 2018). Fire perturbation increased E. horridum seedling establishment more than clearing as also reported previously (Nuche et al, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, the influence of fire on soil fertility showed contradictory results. Some authors reported soil nutrient decreases after prescribed fire events (Martínez-Mena et al, 2001;San Emeterio et al, 2016;Nuche et al, 2018), while others reported neutral or even positive effects on soil nutrients (Fernandes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Badía et al (2017) concluded that burning E. horridum rejuvenates the community which, far from being eliminated, undergoes self-succession in time. Nuche et al (2018) also found that burning E. horridum increases its germination and helps to sow seeds that were not previously present in the rich sub-alpine pastures of the Pyrenees. Ruiz Mirazo et al (2011) state that the current low numbers of livestock in many mountain areas result in the failure of the fire-grazing balance.…”
Section: Combining Extensive Livestock Grazing With Prescribed Fires mentioning
confidence: 91%
“…The mesophytic Pyrenean pastures are composed of subclimax species that require the grazing of shrubs to survive (Halada et al, 2011). As a consequence of grazing reduction, the Pyrenees have suffered shrub encroachment processes, dominated by the thorny cushion dwarf (Echinospartum horridum (Vahl) Rothm), among others (Komac et al, 2013;Nuche et al, 2018). This species forms large and dense monospecific covers (Komac et al,2011) that pose a threat to biodiversity and increase flammability risks (Caballero et al, 2010).…”
Section: Introductionmentioning
confidence: 99%